2018
DOI: 10.3390/nu10081049
|View full text |Cite
|
Sign up to set email alerts
|

Dairy Intake and Acne Vulgaris: A Systematic Review and Meta-Analysis of 78,529 Children, Adolescents, and Young Adults

Abstract: A meta-analysis can help inform the debate about the epidemiological evidence on dairy intake and development of acne. A systematic literature search of PubMed from inception to 11 December 2017 was performed to estimate the association of dairy intake and acne in children, adolescents, and young adults in observational studies. We estimated the pooled random effects odds ratio (OR) (95% CI), heterogeneity (I2-statistics, Q-statistics), and publication bias. We included 14 studies (n = 78,529; 23,046 acne-case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
81
1
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(96 citation statements)
references
References 54 publications
(179 reference statements)
3
81
1
11
Order By: Relevance
“…For example, Ismail, Manaf and Azizan 13 found that drinking milk on at least once per week was linked to increased odds of acne to 3.99 relative to those who drank milk less than once per week while Adebamowo et al 29 found that the intake of whole milk and low fat milk did not significantly influence the odds of acne. However, a meta-analysis review found that the intake of any amount of dairy in general or any kind of milk, regardless of the fat content (full-fat, whole, low-fat, skim) was linked to increased odds of acne 30 , suggesting that dairy and milk intake are likely to influence acne presentation. Possible explanations for this effect implicate steroid hormones or sugars present in milk 21 .…”
Section: Dietary Factors That Influence Acne Presentation the Importmentioning
confidence: 99%
“…For example, Ismail, Manaf and Azizan 13 found that drinking milk on at least once per week was linked to increased odds of acne to 3.99 relative to those who drank milk less than once per week while Adebamowo et al 29 found that the intake of whole milk and low fat milk did not significantly influence the odds of acne. However, a meta-analysis review found that the intake of any amount of dairy in general or any kind of milk, regardless of the fat content (full-fat, whole, low-fat, skim) was linked to increased odds of acne 30 , suggesting that dairy and milk intake are likely to influence acne presentation. Possible explanations for this effect implicate steroid hormones or sugars present in milk 21 .…”
Section: Dietary Factors That Influence Acne Presentation the Importmentioning
confidence: 99%
“…Dark chocolate consumption appears to affect the facial skin of young men by enhancing corneocyte desquamation and promoting bacterial colonization of the residual skin surface components [117]. Any dairy, such as milk, yogurt, and cheese, was associated with an increased OR for acne in individuals aged 7-30 years [20]. Four ounces of shrimp provides about 325 -375 milligrams of omega-3 fatty acids [118].…”
Section: Exhibit 3 Acne Myths/misconception Vs Study Results Myth/mismentioning
confidence: 99%
“…In general, although cow's milk products are rich in calcium, and indeed calcium is one important part of bone strength, there is mixed evidence as to whether dairy foods are helpful or harmful for bone strength or fracture rates [24][25][26]. High dairy consumption carries risks outside of this, for example, milk proteins having been identified as the "dominant causal triggers of type 1 diabetes" [27], and high consumption of cow's milk is associated with increased acne [28]. Conversely, research has also shown diets high in dairy consumption to be associated with either neutral or slightly decreased risks for type II diabetes [29] and coronary heart disease [30], and decreased risk for colon cancer [31].…”
Section: Discussionmentioning
confidence: 99%